Using cumulative carbon budgets and corporate carbon disclosure to inform ambitious corporate emissions targets and long‐term mitigation pathways. (17th August 2022) - Hadziosmanovic, Maida; Lloyd, Shannon M.; Bjørn, Anders; Paquin, Raymond L.; Mengis, Nadine; Matthews, H. Damon
Abstract: With increasing pressure for climate action, commitments to setting scientifically supported emissions targets have become more common among firms. The target‐setting methods currently endorsed by the Science Based Targets Initiative (SBTi) use emission pathways that are aligned with 1.5°C and well‐below 2°C long‐term temperature goals to inform near‐term corporate targets. However, most of these scenarios lead to a temperature overshoot, followed by a return to the temperature goal achieved via net‐negative emissions in the second half of this century. When used to inform near‐term (e.g., 2030) corporate targets, the result is a set of targets that are aligned with an overshoot of a temperature target, with no explicit long‐term commitment to using negative emissions technologies to reverse this. To decrease the risk of this misalignment with the long‐term temperature goal, we propose an alternative approach that derives corporate targets directly from the remaining global cumulative carbon budget. We illustrate this approach using global Scope 1 emissions disclosed by public firms in 2019 to estimate corporate carbon budgets and construct idealized emissions‐reduction pathways that are consistent with the remaining global carbon budget for 1.5°C and well‐below 2°C. While firms, or their sectors, may choose varying mitigation pathways aligned with either global temperature limit, consistency with remaining carbon budgets requires that any delayed mitigation action in the near term is followed by more rapid emissions reductions in subsequent years. This study emphasizes the need for a more precautionary and robust approach to corporate target setting.